Education and training on proper breastfeeding practices for pregnant women: A stunting prevention effort in Pinedapa Village - Christina Entoh; Fransisca Noya; Sony Bernike Magdalena Sitorus; Dafrosia Darmi Manggasa (Universitas Muhammadiyah Magelang, 2024)
The breastfeeding rate in Indonesia is 15.3%. Exclusive breastfeeding coverage in Central Sulawesi in 2021 was 53.5% and in Poso Regency was 51.1%. Exclusive breastfeeding coverage in Pinedapa Village, Poso Coastal District in 2022 was 57%. One of the causes of low breastfeeding rates in Indonesia is the lack of knowledge among pregnant women, families, and the community about the importance of breastfeeding. The most common problem experienced by breastfeeding mothers is sore nipples. This condition usually occurs due to incorrect baby positioning during breastfeeding or incorrect breastfeeding techniques. The purpose of this activity was to improve the knowledge and skills of pregnant women and health cadres on the correct breastfeeding techniques to meet the nutritional needs of infants and thus prevent stunting. The methods used in this community service activity were lectures, discussions, and demonstrations. The results obtained from this activity were that the knowledge of pregnant women and posyandu cadres after the counseling increased to good (100%). The skills of pregnant women and cadres after the training increased from unskilled (0%) to skilled (100%).